Residency patterns and apparent survival in a cavity-nesting bird: population consequences of nest-box supplementation revealed by a long-term study - Francisco Valera; Radovan Václav (Avian Conservation and Ecology, 2021)
Phenotypic plasticity may help organisms persist in modified habitats. Yet, its adaptive value is frequently ignored because fitness consequences are not explored at the required time scale. Taking advantage of a 16-yr nest-box supplementation program, we explored effects of nest type and two social-ecological indices (breeding cluster size and distances between clusters) on adult and offspring survival of a non-excavator cavity-nesting bird species, the European roller (Coracias garrulus), a species of conservation concern. We also investigated site and habitat fidelity associated with different nest types. Apparent survival of rollers was mainly explained by age and sex. Social-ecological factors were more important than cavity type in apparent survival. Increases in apparent survival with decreasing distance to neighboring clusters were comparable for adult males and females but were stronger for juvenile males than for juvenile females. Nest type influenced residency patterns, so that males breeding in nest-boxes were more likely to be recaptured in subsequent years at the study site and in the same nest type compared with males associated with natural and semi-natural nest types. Whereas phenotypic plasticity in nest selection might favor rapid colonization of a novel nest type, widespread use of nest-boxes can decrease, through their effects on site and habitat fidelity, a species' responsiveness to environmental changes. We suggest that nest-box schemes should be applied to promote higher connectiveness of breeding populations and that nest-box programs may influence population dynamics and habitat selection criteria via their effect on social information and natal habitat preference induction.